2020
DOI: 10.1155/2020/8189403
|View full text |Cite
|
Sign up to set email alerts
|

Fabric Defect Detection Using Computer Vision Techniques: A Comprehensive Review

Abstract: There are different applications of computer vision and digital image processing in various applied domains and automated production process. In textile industry, fabric defect detection is considered as a challenging task as the quality and the price of any textile product are dependent on the efficiency and effectiveness of the automatic defect detection. Previously, manual human efforts are applied in textile industry to detect the defects in the fabric production process. Lack of concentration, human fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 77 publications
(134 reference statements)
0
42
0
Order By: Relevance
“…A thorough survey [1] is provided of both two-dimensional and three-dimensional surface defect detection systems for various common metal planar material products such as steel, aluminum, copper plates, and strips. The review [79] presents a detailed overview of histogram-based approaches, color-based approaches, image segmentation-based approaches, frequency domain operations, texturebased defect detection, sparse feature based operations, image morphology operations for fabric defect detection. The survey [80] presents a comprehensive survey on surface defect detection technologies over the last two decades for three typical flat steel products of con-casting slabs, rolled steel strips.…”
Section: Related Workmentioning
confidence: 99%
“…A thorough survey [1] is provided of both two-dimensional and three-dimensional surface defect detection systems for various common metal planar material products such as steel, aluminum, copper plates, and strips. The review [79] presents a detailed overview of histogram-based approaches, color-based approaches, image segmentation-based approaches, frequency domain operations, texturebased defect detection, sparse feature based operations, image morphology operations for fabric defect detection. The survey [80] presents a comprehensive survey on surface defect detection technologies over the last two decades for three typical flat steel products of con-casting slabs, rolled steel strips.…”
Section: Related Workmentioning
confidence: 99%
“…Czimmermann et al presented a detail review based on automatically detection of fabric faults and fabric defect [ 71 ]. Rasheed et al reported a comprehensive study on faults detection methods of textiles [ 72 ]. The widely used detection methods are based on image segmentation, color coordinates, frequency domain, texture-based, image morphology operations and deep learning.…”
Section: Classification Based On Textile Processesmentioning
confidence: 99%
“…Among the various commonly used evaluation metrics, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and their denotations are discussed in the succeeding section [32]. PPV is the proportion of positive results that are true positive and is also known as precision.…”
Section: Error Matrixmentioning
confidence: 99%